Enforcing Political Neutrality among Contract-Based Government Employees (PPPK) in Local Elections: A Case Study of Purbalingga Regency - Mafit Sumantri, Jufri; Kunarti, Siti; Sudrajat, Tedi (LPPM Universitas Harapan Bangsa, 2025)
The enforcement of political neutrality among contract-based government employees (PPPK) presents complex legal and institutional challenges within Indonesia’s decentralized administrative system. This study critically examines the legal, constitutional, and cultural dimensions of PPPK neutrality during regional elections, with a particular focus on the case of Purbalingga Regency. Using a socio legal methodology, the research combines doctrinal, normative, and empirical approaches to assess the effectiveness of existing legal instruments, primarily Law Number 20 of 2023, and their practical application in local governance settings. The analysis draws on interviews, survey data, and field observations to evaluate the institutional capacity of civil service bodies such as BKD, KASN, and Panwaslu, as well as the role of civil society in oversight. The findings reveal significant enforcement gaps caused by regulatory ambiguity, overlapping institutional mandates, and limited internalization of neutrality as a professional ethic. Although neutrality is legally required, its implementation is constrained by legal uncertainty related to PPPK’s dual identity as both public officials and holders of constitutional rights. The study argues that enforcement must move beyond formal legal provisions to include cultural legitimacy, institutional coordination, and adaptation to digital era challenges. Drawing on the legal doctrine of proportionality and the concept of law as a living institution, the study recommends regulatory reform, structured ethical training, and participatory monitoring mechanisms to promote accountability and safeguard democratic integrity within the civil service.